Miami's criminal past uncovered - Bustos, Sergio (History Press, 2007)
The unsolved murder of six-year-old Judith Ann Roberts -- Miami, the beginning of the end for Doors legend Jim Morrison -- Murder of a Union boss in Miami -- The mass murderer who didn't get away -- Christopher Wilder, model murderer -- Andrew Cunanan and Gianni Versace meet in South Beach for murder